STATE OF HUMORAL IMMUNITY IN WOMEN WITH NEOPLASTIC DISEASES OF THE UTERUS - A. V. Efremov; N. A. Matveevskij; A. N. Trunov; I. D. Safronov (Акушерство, гинекология и репродукция, 2016)
The purpose of this study was to examine changes in indicators that reflect the activation of the humoral immune system, the severity of the destructive processes and autoimmune reactions in patients with neoplastic diseases of the uterus. The testing revealed significantly higher concentrations of IgA, the levels of circulating immune complexes and antibodies to antigens of native DNA. The findings suggest the importance of the activation of immune (autoimmune) reactions and destructive processes in pathogenetic mechanisms of development of uterine fibroids and cancer of the uterus.